The characteristic and clinical profiles among COVID-19 patients at the National Emergency Hospital Wisma Atlet Jakarta in 2021 - Misriani; Muchamat Helmi; Arif Sujagat; Lutfi Rinaldi Syahbana; Wahyu Setiyowati; Tjahja Nurobi; Budiman; Tri Setyanti; Imelda Sussanti; Dianita Sugiyo; Noven Tri Wandasari; Faudyan Eka Satria (Jurnal Cakrawala Promkes, 2023)
The World Health Organization designated Covid-19, caused by SARS-COV-2, a worldwide pandemic on March 11, 2020, and it has been entering Indonesia since early March 2020. This study attempts to elucidate and map patients' profiles and essential emergency preparedness measures during a national crisis. This research used an exploratory descriptive technique with structured interviews to collect data on retrospective data from hospital patients. The ethical clearance was issued prior to data collection, and informed permission was in accordance with the ethical clearance. The total number of patients treated in the COVID-19 National Emergency Hospital Wisma Atlet Kemayoran (RSDCWAK) was 69,965, and structured interviews were conducted with 46,408 patients. Demographic data of the patients consisted of 49.06% female and 50.04% male patients. Patients were aged 20-49 years (68.08%), and 76.05% of patients had mild symptoms. Hypertension was the highest comorbid at 6.11%, with common symptoms experienced. Most patients received vaccines (34.14%) with the highest type of vaccine (Sinovac 22.26%). To minimize the spread of COVID-19, RSDC WAK has implemented a zoning policy in its building, including red for COVID-19 patients with a risk of severe infection, yellow for patients with risk of mild infection, and green for areas free of COVID-19 and forbidden for COVID-19 patients. The COVID-19 pandemic has become a global health problem. The COVID-19 pandemic has become a global health problem. No one knows when the COVID-19 pandemic will end because the virus constantly changes and creates new variants. Proper regulations and human resources are required to have the readiness to control COVID-19. Zoning is the most appropriate way to prevent the spread of COVID-19 at RSDCWAK.